Financial crisis, trade finance, and SMEs: Case of Central Asia - Gloria O. Pasadilla (Asian Development Bank Institute (ADBI), 2010)
This paper surveys studies of the importance of Central Asian small- and medium-sized enterprises (SME) in the economy and their experience during the Russian financial crisis. It also uses survey data from the World Bank and the European Bank for Reconstruction and Development's Business Environment and Enterprise Performance Surveys to infer noteworthy characteristics, features, and dependencies on financing of Central Asian SMEs and, consequently, derive the potential impact of the crisis on the sector. The paper also assesses government support for SMEs and the necessary market reforms that will give a boost to the sector's development in the region.
Keywords: E44; G01; G18; G28; G38; 330; Finanzmarktkrise; Russland; Makroökonomischer Einfluss; Wirtschaftliche Anpassung; Klein- und Mittelunternehmen; Zentralasien